Minimnya Pengetahuan HIV/AIDS Remaja Wilayah Perbatasan: Ancaman Serius Di Era Digital - Rusmiati; Nurul Fatimah Azzarah; Nur Yola Salsabila; Lutfi Dwy Adinda; Kamelia Ananditha; Siti Itsnah Mardiyah; Rika Septiani (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Adolescents are highly vulnerable to HIV/AIDS due to limited knowledge, widespread misinformation, and the lack of comprehensive sex education in Indonesia. Tarakan City records the highest HIV/AIDS cases in North Kalimantan, with adolescents as a significant contributor. This study aims to analyze adolescents’ knowledge of HIV/AIDS and the multidimensional factors influencing it, including geographical, sociocultural, educational, and psychosocial aspects. This study uses a descriptive-qualitative approach based on literature review and secondary data, analyzed thematically. Results show that low sexual literacy among adolescents is driven by inadequate sex education, social stigma, limited access in remote areas (3T), and digital misinformation. These factors contribute to risky sexual behavior, low HIV testing awareness, and mental health issues. HIV/AIDS prevention among adolescents requires a multisectoral approach, including school- and culture-based sex education, digital literacy improvement, youth-friendly health services, and active adolescent involvement. Cross-sector collaboration is crucial to building an informed, protected, and empowered young generation.